2004
DOI: 10.1111/j.1750-3639.2004.tb00085.x
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia Leads to Apoptosis—and Necrosis‐like Neuron Death in the Ischemic Rat Hippocampus

Abstract: Morphological evidence of apoptosis in transient forebrain ischemia is controversial. We therefore investigated the time sequence of apoptosis-related antigens by immunohistochemistry and correlated it with emerging nuclear patterns of cell death in a model of transient forebrain ischemia in CA1 pyramidal cells of the rat hippocampus. The earliest ischemic changes were found on day 2 and 3, reflected by an upregulation of phospho-c-Jun in a proportion of morphologically intact CA1 neurons, which matched the nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 58 publications
2
50
0
1
Order By: Relevance
“…One is that the neurons of CA1 died a caspase-dependent death, but the presence of cleaved caspase-3 in the CA1 pyramidal layer had declined at 3 days after the ischemic insult, since previous studies reported that caspase-3 was activated as early as 30 min and declined at 24 h and afterwards following cerebral ischemia (Cho et al, 2003;Namura et al, 1998). Another explanation is that the majority of the ischemic CA1 neurons follow a caspase-independent necrosis-like death (Muller et al, 2004), while the neurons in DG area follow a caspase-dependent apoptosis pathway. In addition, compared with WT mice, there were fewer TUNEL positive cells and less activation of caspase-3 in HF in TLR4 -/-mice subjected to GCI/R (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…One is that the neurons of CA1 died a caspase-dependent death, but the presence of cleaved caspase-3 in the CA1 pyramidal layer had declined at 3 days after the ischemic insult, since previous studies reported that caspase-3 was activated as early as 30 min and declined at 24 h and afterwards following cerebral ischemia (Cho et al, 2003;Namura et al, 1998). Another explanation is that the majority of the ischemic CA1 neurons follow a caspase-independent necrosis-like death (Muller et al, 2004), while the neurons in DG area follow a caspase-dependent apoptosis pathway. In addition, compared with WT mice, there were fewer TUNEL positive cells and less activation of caspase-3 in HF in TLR4 -/-mice subjected to GCI/R (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Increasing evidence has suggested that ischemic brain injury induces neuronal apoptosis (Bi et al, 2006;Muller et al, 2004). In this study, TUNEL and neuron doublestaining was performed to examine whether roscovitine can reduce neuronal apoptosis after MCAO.…”
Section: Roscovitine Inhibits Neuronal Apoptosis and Provides Neuroprmentioning
confidence: 99%
“…In the latter case, specific differentiation between apoptotic and necrotic cell death is frequently requested, which is problematic based only on microscopic morphology. This is best illustrated by the longstanding controversy whether postischemic delayed neuronal death of vulnerable hippocampal neurons is apoptotic or necrotic (Deshpande et al, 1992;Muller et al, 2004;Wei et al, 2006). Another major challenge is reliable detection of early ischemic changes.…”
Section: Light Microscopy and Macroscopymentioning
confidence: 99%